Ontologi dan Epistemologi Lulik: Menelusuri Fondasi Filosofis dalam Kosmologi Masyarakat Timor-Leste - Alberto Alves Pereira; Pawennari Hijjang; muhammad Basir; Ahmad Ismail (Universitas Cenderawasih, 2026)
ABSTRACT Studies on East Timorese culture have largely been dominated by exotic anthropological approaches or post-conflict socio-political analyses. Consequently, the metaphysics and indigenous knowledge systems of the society have rarely been systematically formulated within formal philosophical discourse. This study aims to examine how the concept of Lulik (the sacred) operates as an ontological foundation underlying the nature of being, as well as an epistemological basis that directs the way of knowing and validating the order of truth in the cosmology of the East Timorese people. As a philosophical inquiry rooted in ethno-philosophy, this study employs a critical literature review method utilizing a philosophical hermeneutics approach to profoundly interpret ethnographic texts, cultural symbols, and traditional structures of Timor-Leste. The findings indicate that Lulik is neither a mere myth, superstition, nor a primitive religious taxonomy, but rather a sophisticated ontological structure that determines the hierarchy of existence and the integral relationship between humans, nature, and ancestors (mate-bian). Furthermore, in the epistemological dimension, Lulik functions as a moral foundation and a performative truth-bearing instrument that validates ethical frameworks, customary laws (lisan), and the navigation of everyday life. This philosophical reconstruction underscores the urgency of positioning indigenous belief systems as independent philosophical structures in the decolonization of knowledge in Southeast Asia. Keywords: Lulik, ontology, epistemology, cosmology, Timor-Leste, cultural philosophy.